Errors in the Use of Prepositions by Maithili Learners of English and Their Remedies - Jha, Amar Kant (Tribhuvan University Journal, 2010)
The present paper attempts to describe the errors in the use of prepositions by Maithili learners of English, account for them in the light of the Speakers L 1, L 2, interferences and other teaching-learning strategies, and suggest their remedies. I lately lost a preposition; It hid, I thought, beneath my chair And angrily I cried: "perdition!" Up from out of in under there! Morris Bishop: "The Naughty preposition!" A Bowl of Bishop. Key words: Prepositions errors; Maithili; English Tribhuvan University Journal Volume XIV, 1991 Page: 49-57 Uploaded date: 5 October, 2010